Three Siblings With an Attenuated Presentation of Perlman Syndrome: A Case Report and Literature Review - Alayne P. Meyer; Daniel C. Koboldt; Swetha Ramadesikan; Kristin Zajo; Maria E. Hernandez Gonzalez; Anthony R. Miller; Douglas Depoorter; Catherine P. Comer; James I. Geller; Katherine Somers; Nilay Shah; Marco L. Leung (Molecular Genetics & Genomic Medicine)
ABSTRACT Introduction Perlman syndrome is a rare autosomal recessive overgrowth disorder with a predisposition to Wilms tumor, caused by biallelic variants in DIS3L2. The majority of patients die in infancy due to respiratory and/or renal failure, limiting the reports of patients surviving into childhood. Methods Exome sequencing was performed in the proband and her older brother. A younger sibling subsequently underwent targeted variant analysis. RNA sequencing was utilized to investigate the functional impact of the missense variant. Results Three siblings presented at birth with fetal macrosomia, dysmorphic facial features, and facial hypotonia. The proband had early speech delay and was diagnosed with Wilms tumor at 3 years old. Her brothers both had developmental delay presenting within the first year of life. Genetic testing identified compound heterozygous variants in DIS3L2 (NM_152383.5): c.127C>T (p.Arg43Ter) (paternal)/c.2381G>A (p.Arg794His) (maternal). Conclusion Our findings expand the genetic and clinical spectrums associated with Perlman syndrome and increase the understanding of the phenotype observed in childhood. They also support consideration of genetic testing for Perlman syndrome in individuals and sibships with macrosomia, developmental delay, and characteristic facial dysmorphisms, with or without the presence of Wilms tumor.